1994
DOI: 10.1093/nar/22.7.1221
|View full text |Cite
|
Sign up to set email alerts
|

Extremely short 20–33 nucleotide introns are the standard length inParamecium tetraurelia

Abstract: Paramecium tetraurelia has the shortest known introns as its standard intron length. Sequenced introns vary between 20 and 33 nucleotides in length. The intron sequences were discovered in genomic sequences coding for a variety of different proteins, including phosphatases, kinases, and low-molecular weight GTP-binding proteins. All intron sequences begin with the conserved dinucleotide GT and end with the conserved dinucleotide AG. The sequences are more AT rich than the Paramecium coding sequences. The ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 33 publications
4
50
0
Order By: Relevance
“…of the translation initiation codon); in DHC-8, the intron begins at nucleotide 170. As in other Paramecium genes (Russell et al, 1994) the identified introns are short (23-28 nucleotides) and conform to the GT-AG rule for splicing (reviewed in Moore et al, 1993). It is possible that other introns, which do not alter the reading frames, are present in both genes.…”
Section: Resultsmentioning
confidence: 86%
“…of the translation initiation codon); in DHC-8, the intron begins at nucleotide 170. As in other Paramecium genes (Russell et al, 1994) the identified introns are short (23-28 nucleotides) and conform to the GT-AG rule for splicing (reviewed in Moore et al, 1993). It is possible that other introns, which do not alter the reading frames, are present in both genes.…”
Section: Resultsmentioning
confidence: 86%
“…A comparison of the genomic sequence with their cDNA equivalent revealed six introns of 22 bp, 23 bp, 25 bp, 27 bp, 28 bp and 29 bp (Fig. 1A), a length typical for Paramecium (Russell et al, 1994;Sperling et al, 2002). The gene was named IP 3 R N (accession number CR932323).…”
Section: Resultsmentioning
confidence: 99%
“…Other than in piroplasmids, such tiny introns have not been demonstrated in the CCTη gene from alveolates such as the apicomplexans Toxoplasma, Neospora, and Plasmodium and the ciliate Tetrahymena. Comparatively small (25 to 29 nt) introns reside in the CCTη gene of ciliate Paramecium (GenBank accession number NC_006058), and the tiny introns (~19 to 23 nt) have been reported in macronuclear genome of Paramecium [29] and nucleomorph genome of chlorarachniophytes [7]. Gilson et al surmised that the tiny introns in chlorarachniophytes may originate as miniaturizations of the larger introns present in the endosymbiont at the time of capture [7].…”
Section: Discussionmentioning
confidence: 99%